Raoultella planticola bacteremia-induced fatal septic shock following burn injury - Tetsuya Yumoto; Hiromichi Naito; Hiromi Ihoriya; Kohei Tsukahara; Tomoyuki Ota; Toshiyuki Watanabe; Atsunori Nakao (BMC, 2018)
Abstract Background Raoultella planticola, a Gram-negative, aerobic bacillus commonly isolated from soil and water, rarely causes invasive infections in humans. Septic shock from R. planticola after burn injury has not been previously reported. Case presentation A 79-year-old male was admitted to the emergency intensive care unit after extensive flame burn injury. He accidently caught fire while burning trash and plunged into a nearby tank filled with contaminated rainwater to extinguish the fire. The patient developed septic shock on day 10. The blood culture detected R. planticola, which was identified using the VITEK-2 biochemical identification system. Although appropriate antibiotic treatment was continued, the patient died on day 12. Conclusions Clinicians should be aware of fatal infections in patients with burn injury complicated by exposure to contaminated water.